2023
DOI: 10.1021/acs.langmuir.3c00402
|View full text |Cite
|
Sign up to set email alerts
|

Time Evolution of Ultrasmall Gold Nanoparticle–Protein Interactions

Abstract: To date, much effort has been devoted toward the study of protein corona formation onto large gold nanoparticles (GNPs). However, the protein corona concept breaks down for GNPs in the ultrasmall size regime (<3 nm), and, as a result, our understanding of ultrasmall GNP (usGNP)–protein interactions remains incomplete. Herein, we used anionic usGNPs and six different proteins as model systems to systematically investigate usGNP–protein interactions, with particular focus on the time evolution and long-term beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Blood compatibility is a critical requirement for NPs that are administered intravenously. Importantly, we note that the absence of a hard protein corona on the NP surface does not in itself ensure blood compatibility. This is because transient NP interactions with proteins are capable of interfering with protein function and biochemical pathways, potentially triggering toxic responses. , , Moreover, NP interactions with the plasma membrane of blood cells can also perturb their normal functions. Therefore, a comprehensive evaluation of blood compatibility is necessary to assess potential risks associated with NP administration in vivo. , This assessment should include several complementary assays, including the hemolysis of red blood cells, platelet aggregation, leucocyte activation, and endothelial cell cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood compatibility is a critical requirement for NPs that are administered intravenously. Importantly, we note that the absence of a hard protein corona on the NP surface does not in itself ensure blood compatibility. This is because transient NP interactions with proteins are capable of interfering with protein function and biochemical pathways, potentially triggering toxic responses. , , Moreover, NP interactions with the plasma membrane of blood cells can also perturb their normal functions. Therefore, a comprehensive evaluation of blood compatibility is necessary to assess potential risks associated with NP administration in vivo. , This assessment should include several complementary assays, including the hemolysis of red blood cells, platelet aggregation, leucocyte activation, and endothelial cell cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…This is because transient NP interactions with proteins are capable of interfering with protein function and biochemical pathways, potentially triggering toxic responses. 49 , 58 60 , 70 72 Moreover, NP interactions with the plasma membrane of blood cells can also perturb their normal functions. Therefore, a comprehensive evaluation of blood compatibility is necessary to assess potential risks associated with NP administration in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Lately, there has been a vigorous renewal of interest in understanding protein interactions with surfaces of nanoparticles which has, again, importance in both in vivo and in vitro (Gupta & Roy, 2020; Mukherjee & Gupta, 2016a; Sousa et al, 2021). This also includes binding of IDRs to nanoparticles (Lima et al, 2023; Mahapatra et al, 2020; Munari et al, 2020). Viola et al reported that interaction of tau protein with ultrafine gold nanoparticles led to multimolecular assembly via hot spots of binding sites as in PPI interactions (Viola et al, 2022).…”
Section: Interactions Of Idps/idrs With Other Proteins and Surfaces I...mentioning
confidence: 99%
“…Here, the analogy becomes even more pertinent due to the small size and high surface curvature of usNPs, which provide a limited binding interface for protein interactions. Hence, when proteins interact with usNPs, significant protein spreading and denaturation on the usNP surface are unlikely [99][100][101], and major lateral interactions between bound proteins are also improbable. In fact, usNPs with a diameter of 1.5 nm or less may be so small as to bind only to a single protein (Figure 6A) [95].…”
Section: Kinetics Of Protein Interactions With Ultrasmall Npsmentioning
confidence: 99%